Key challenges for monetary policy - Rainer Haselmann; Florian Heider; Loriana Pelizzon; Michael Weber (Leibniz Institute for Financial Research SAFE, 2025)
Monetary policy in the euro area faces significant challenges due to the evolving economic landscape marked by the return of inflation, financial instability risks, and the consequences of unconventional monetary policy (UMP) to the operational framework of monetary policy. This article evaluates these key challenges in the context of the European Central Bank's (ECB) mandate and its broader implications. It highlights the unprecedented resurgence of inflation, which has complicated monetary policy decisions and revealed gaps in understanding household inflation expectations. Financial stability, now integral to the ECB's mandate, is strained by trade-offs between short-term and long-term stability, particularly under high-interest rate environments. Finally, UMP has disrupted traditional financial mechanisms and increased dependency on the central bank's liquidity operations.
Keywords: 330; Monetary Policy; Inflation; Financial Stability; Balance Sheet